1999
DOI: 10.1002/(sici)1099-0739(199902)13:2<113::aid-aoc837>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic speciation including ‘hidden’ arsenic in natural waters

Abstract: Recent studies indicate the existence in natural waters of 'hidden' arsenic which had previously been undetected by the hydride generation technique. A speciation method for arsenic species has been developed in which hidden arsenic was classified into two fractions by their lability to the photochemical degradation procedure: the ultraviolet-labile fraction and the ultravioletresistant fraction. The ultraviolet-labile fraction was the major fraction of hidden arsenic and comprised 15-45% and 4-26% of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The dynamics of arsenate exchange between water and adsorbing colloids are analogous to those [20]. Arsenate and dimethylarsinic acid (DMAA) are the major species of arsenic in toxic aquatic systems [21]. Uptake behavior of these two arsenic species could reflect the influence of inorganic and organic arsenic species and their interactions with PO 4 3− and Fe ions.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of arsenate exchange between water and adsorbing colloids are analogous to those [20]. Arsenate and dimethylarsinic acid (DMAA) are the major species of arsenic in toxic aquatic systems [21]. Uptake behavior of these two arsenic species could reflect the influence of inorganic and organic arsenic species and their interactions with PO 4 3− and Fe ions.…”
Section: Introductionmentioning
confidence: 99%
“…In lake waters from Ontario, Azcue and Nriagu (1995) found As(III) concentrations of 7-75 µg/L, As(V) of 19-58 µg/L and organic As of 0.01-1.50 µg/L (DMAA, MMAA were dominant). The role of organic species may be more important close to the sediment-water interface (Hasegawa et al, 1999). In groundwaters, As(III) was dominant in most of the detected samples (53-98%) (Kim et al, 2002).…”
Section: Arsenic Speciation In Natural Water Environmentmentioning
confidence: 96%
“…However, it was reported that this interference was efficiently eliminated by collision of ArCl molecules with helium introduced prior to mass spectrometer in reaction cell (Nakazato et al, 2002). These analytical procedures enabled the highly sensitive determination of As(V), As(III), MMAA and DMAA at pg/mL level (Cabon and Cabon, 2000;Featherstone et al, 2000;Hasegawa et al, 1999) in seawater samples (even a large volume (200 mL)) by ion-exclusion chromatography (polystyrene resin, dilute nitric acid at pH = 2.0 as the eluent) combined with HG-ICP-MS (Nakazato et al, 2002). The method is easy to operate and no sample pre-treatment is needed.…”
Section: Arsenic Speciation Hyphenated Techniquesmentioning
confidence: 99%
“…However, natural abundance of inorganic As species are higher. It is well known that arsenite (AsO 3 3− ) and arsine (AsH 3 ) dominate at reducing atmosphere while arsenate (AsO 4 3− ) in oxygenized environments [2,3]. Consumption of low levels As over a longer period is harmful with a high risk of cancer [4].…”
Section: Introductionmentioning
confidence: 99%